Directed evolution of P-glycoprotein cysteines reveals site-specific, non-conservative substitutions that preserve multidrug resistance. Issue 3 (25th June 2014) - Swartz, Douglas J.; Mok, Leo; Botta, Sri K.; Singh, Anukriti; Altenberg, Guillermo A.; Urbatsch, Ina L.
Abstract : Directed evolution of Cys (cysteines) in the multidrug transporter Pgp identified novel non-conservative substitutions, revealed important domain interactions and produced a CL protein that is more robust and active than previous CL Pgp built solely on conservative alanine substitutions. Abstract : Pgp (P-glycoprotein) is a prototype ABC (ATP-binding-cassette) transporter involved in multidrug resistance of cancer. We used directed evolution to replace six cytoplasmic Cys (cysteine) residues in Pgp with all 20 standard amino acids and selected for active mutants. From a pool of 75000 transformants for each block of three Cys, we identified multiple mutants that preserved drug resistance and yeast mating activity. The most frequent substitutions were glycine and serine for Cys 427 (24 and 20%, respectively) and Cys 1070 (37 and 25%) of the Walker A motifs in the NBDs (nucleotide-binding domains), Cys 1223 in NBD2 (25 and 8%) and Cys 638 in the linker region (24 and 16%), whereas close-by Cys 669 tolerated glycine (16%) and alanine (14%), but not serine (absent). Cys 1121 in NBD2 showed a clear preference for positively charged arginine (38%) suggesting a salt bridge with Glu 269 in the ICL2 (intracellular loop 2) may stabilize domain interactions. In contrast, three Cys residues in transmembrane α-helices could be successfully replaced by alanine. The resulting CL (Cys-less) Pgp was fully active in yeast cells, and purified proteins displayed drug-stimulated ATPase activities indistinguishable from WT (wild-type) Pgp. Overall, directed evolution identified site-specific, non-conservative Cys substitutions that allowed building of a robust CL Pgp, an invaluable new tool for future functional and structural studies, and that may guide the construction of other CL proteins where alanine and serine have proven unsuccessful.